Navigating dual crises: mental health of Czech health care workers during the Ukrainian refugee influx and COVID-19 pandemic - Miroslava Janoušková; Jana Šeblová; Pavla Brennan Kearns; Matěj Kučera; Marie Kuklová; Jaroslav Pekara; Dominika Seblova (European Journal of Psychotraumatology)
Background: European health care workers recently experienced serious challenges to their mental health. Following the extremely stressful experience of the COVID-19 pandemic, the war in Ukraine caused a humanitarian influx of refugees in need of social and healthcare. We aimed to explore: (1) how working with refugees has affected the mental well-being of health care workers in the context of the COVID-19 pandemic, and (2) the nature of health care workers’ emotional strain related to the refugee situation and the war in Ukraine.Methods: We used a combination of quantitative regression analyses and qualitative content analysis to assess data collected by an online questionnaire in 2022. The study included 1121 health care workers from the Czech arm of the international HEROES Study.Results: Quantitative findings did not indicate that working with Ukrainian refugees was reliably associated with a greater occurrence of symptoms of depression, anxiety, distress, or burnout. Qualitative analysis revealed five categories of emotional strain: impacts on working conditions, emotional reactions to refugees and the war, comparisons with the COVID-19 pandemic, and coping strategies.Conclusions: This study highlights the resilience of health care workers but also points to the need for ongoing support to address the complex emotional challenges they face during health crises.